The determinants of brain drain in developing countries - Ngoma, Abubakar Lawan; Ismail, Normaz Wana (Emerald Group Publishing, 2013)
Purpose: Skilled migrant workers move relatively in unidirectional form (from developing to developed countries) in response to many factors. The purpose of this paper is to examine some factors that influence skilled migration to such preferred locations among skilled workers. Design/methodology/approach: Both conceptual discussion and analytical approach are used. Findings: The authors' econometric model identified an inverted U‐shaped relationship between skilled migration rates, wage differentials and income convergence with destination countries. Other factors found to be significantly related to brain drain are population size, domestic political instability and distance to destination countries. Originality/value: This paper presents insights on factors influencing migration decisions among skilled migrants and why skilled workers' migration from developing countries remains on the increase over the years, despite the urgent need for highly skilled personnel in most of these countries.